EVALUATION OF ORGANOLEPTIC AND PHYSICAL OF SCRUB CREAM WITH CHICKEN EGGSHELL POWDER ADDITVE THROUGH YOGHURT SOAKING - B. K., Mirsani; Miwada, I N. S.; Putri, B. R. T. (Jurnal Peternakan Tropika; Vol 12 No 3 (2024): Vol. 12 No. 3 Tahun 2024; May - June, 2024)
Chicken eggshell is an agricultural waste that has polluted the environment, so it needs to be used as a product, namely scrubbing cream by soaking with yogurt. This study aims to determine the effect of soaking time of chicken eggshell powder using yogurt as an additional ingredient of scrub cream with different concentrations. This study used a completely randomized design (CRD) factorial pattern with two factors assessed by 20 semi trained panelists. The first factor is the soaking time of chicken eggshell powder using yoghurt namely; chicken eggshell without yoghurt soaking (P0); soaking for 15 minutes (P1); 30 minutes (P2); 45 minutes (P3); and 60 minutes (P4). The second factor was the concentration of chicken eggshell powder namely; 6% concentration (F1) and 18% concentration (F2). The observed variables were organoleptic evaluation (texture, aroma, consistency, and overall acceptance) and physical properties (pH) which were analyzed using Kruskal Wallis analysis and continued with Man Whitney test. The results of the organoleptic test showed that the soaking time of chicken eggshell powder using yogurt was significantly different (P<0.05) to the texture and overall acceptance and not significantly different to the aroma and consistency of scrub cream (P>0.05). While the results of the physical test showed that the concentration of chicken eggshell powder was significantly different (P<0.05) on pH. The conclusion is that soaking chicken eggshell powder using yoghurt is significantly different (P<0.05) on pH. Based on the results of the study, it can be concluded that soaking chicken eggshell powder using yogurt can improve the organoleptic quality of scrub cream on texture and overall acceptance, while the concentration of chicken eggshell powder can improve the physical quality of scrub cream and there is an interaction between the two factors on texture. In addition, the F1P4 and F2P4 treatments were the highest overall acceptance and favored by panelists.